Modelagem simplificada de gerador fotovoltaico para simulação dinâmica de redes com integração de geração distribuída em condições normais e anormais de operação - Queiroz, Luann Georgy Oliveira (2023)
The massive integration of Distributed Generation (DG) can lead to modifications in the electric power distribution system, altering parameters related to voltage profile, system stability, and short-circuit levels. From this perspective, the use of tools enabling a better understanding of these impacts becomes fundamental. The dynamic modeling of distributed generators is introduced in this context, being employed to simulate the behavior of these systems, providing a deeper understanding of their performance. In this sense, this work initially presents a modeling methodology for distributed generators suitable for the dynamic simulation of electric power systems with integrated photovoltaic distributed generators, titled the “Photovoltaic Simplified Model” (PVSiM). Through simplified modeling, aiming for greater ease of implementation and reduced computational effort, the proposed model represents the photovoltaic system as a current source, encompassing three main variables: active power output of the photovoltaic generator, power factor, and voltage at the Point of Common Coupling (PCC). To validate the system, comparisons were made with other models already existing in the literature and with actual data from a photovoltaic power plant. Additionally, the model presents three different versions that seek to incorporate into the system the guidelines established by NBR 16149 regarding the connection of photovoltaic generators to the distribution network. Thus, different modes of operation of the distributed generator were developed, considering both normal and abnormal operation indices, according to variations in voltage and frequency: 7 different operating modes were created based on voltage levels at the PCC (MOPV), and another 4 modes were designed to address variations in the grid frequency (MOPF). The actions of the operating modes allowed for the shutdown, disconnection, or reconnection of the DG to the grid, as well as enabling the reduction or increase of active power supplied to the load. The analyses conducted, considering scenarios with and without short circuits, demonstrated satisfactory performance of both the simplified model and the versions for abnormal operation scenarios, where the correct functioning of the different operating modes created was verified, complying with the regulations of NBR 16149.